The French Revolution : a Tale of Terror and Hope for Our Times. - Behr, Harold (Sussex Academic Press, 2015)
This is the story of the French Revolution told from a psychological and group dynamic perspective. The aim is to throw light on the workings of the revolutionary mind and the emotions at work in society which pave the way towards revolution and war. Louis XVI and Marie Antoinette are presented as a couple trapped by the symbolism invested in them, a circumstance that turned them into scapegoats. The contrasting personalities of the two most controversial leaders of the Revolution Robespierre and Danton provide psychologically informed explanations of their success and failure as leaders.
Keywords: Revolutions -- France -- Psychological aspects.; Revolutionaries -- France -- Psychology.; France -- History -- Revolution, 1789-1799 -- Psychological aspects.; Révolutions -- France -- Aspect psychologique.; Révolutionnaires -- France -- Psychologie.; HISTORY -- Europe -- France.; Psychological aspects; Revolutionaries -- Psychology; Revolutions -- Psychological aspects; France; 1789-1799; History